Development of non-linear controllers for a tri-state boost converter - Chan, C. Y. (2013)
The development of non-linear controllers for a tri-state boost converter in the presence of an unknown load is addressed. In contrast to the conventional boost converter, the tri-state boost converter has two control inputs and does not have a right-half-plane zero. The controllers are designed using the average model of the tri-state boost converter to vary both the `boost` and `capacitor-charging` intervals using the average model of the tri-state boost converter to achieve fast response and a small inductor current. Experimental results to illustrate the features of the controllers are provided.